DIREWOLF: A FRAMEWORK FOR WIDGET-BASED DISTRIBUTED USER INTERFACES - KOVACHEV, DEJAN; RENZEL, DOMINIK; NICOLAESCU, PETRU; KOREN, ISTVAN; KLAMMA, RALF (Journal of Web Engineering, 2014)
Web applications have overcome traditional desktop applications especially in collab- orative settings. However, the bulk of Web applications still follow the user on a single device" computing model. Therefore, we created the DireWolf framework for rich Web applications with distributed user interfaces (DUIs) over a federation of heterogeneous commodity devices supporting modern Web browsers such as laptops, smart phones and tablet computers. The DUIs are based on widget technology coupled with cross-platform inter-widget communication (IWC) and seamless session mobility. Inter-widget communication technologies connect the widgets and enable real-time col- laborative applications as well as runtime migration in our framework. We show that the DireWolf framework facilitates the use case of DUI-enabled semantic video annotation. For a single user it provides more exible control over di erent parts of an application by enabling the simultaneous use of smart phones, tablets and computers. We con- ducted a technical evaluation and two user studies to validate the DireWolf approach. The work presented opens the way for creating distributed Web applications which can access device speci c functionalities such as multi-touch, text input, etc. in a federated and usable manner. In this paper, we also sketch our ongoing work to integrate the WebRTC API into DireWolf, where we see opportunities for potential adoption of DUI Web applications by the majority of Web users.